Metabolic fate of SCE-1365, a new broad-spectrum cephalosporin, after parenteral administration to rats and dogs. - Tanayama, S (1980)
Disposition of [14C]SCE-1365 was studied in rats and dogs after intramuscular or intravenous injection. The plasma level of [14C]SCE-1365 peaked at 15 min after intramuscular administration and declined rapidly to give half-lives of 27 and 39 min, respectively, in rats and dogs. After intravenous dosage, half-lives were 22 and 32 min, respectively, in rats and dogs. In both animals, the plasma levels of 14C were made up largely of unchanged antibiotic. Binding to plasma protein was 91 and 31%, respectively, in rats and dogs. Tissue levels of [14C]SCE-1365 administered intramuscularly to rats peaked at 15 min and were highest in the kidney and lowest in the brain, with plasma, liver, lung, heart, intestinal wall, and adrenal gland occupying intermediary positions in the order listed. The concentration of [14C]SCE-1365 in erythrocytes was very low, as was the level of the antibiotic in rat fetuses. The milk of rats given [14C]SCE-1365 intramuscularly contained detectable levels of 14C. [14C]SCE-1365 was completely eliminated from the bodies of rats and dogs within 24 to 48 h. In both animals, a large amount of the dosed 14C was excreted in urine as unaltered antibiotic. The remainder was eliminated in the feces via bile. In rats, [14C]SCE-1365 was eliminated by both glomerular filtration (33%) and tubular secretion (67%). An active transport process appeared to be involved in biliary excretion in rats.